PELATIHAN PENULISAN KONTEN EDUKASI KESEHATAN BERBAHASA INDONESIA UNTUK MEDIA SOSIAL di PUSKESMAS - juliana; Harahap, Olivia; Zebua, Sherli Rahmadani; Retno Desti Dwi Meilasari; Elfi Husnita (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
The development of digital technology has encouraged health professionals to effectively deliver health information through social media. However, many health education contents are still presented in rigid, technical, and less communicative language, making them difficult for the general public to understand. This community service activity aims to improve the skills of community health center (Puskesmas) personnel in writing health education content using simple, clear, and engaging Indonesian language. The implementation methods included practice-based training, mentoring in content creation, and publication on the official social media platforms of the Puskesmas. The results of the activity show an increase in participants’ ability to compose more communicative, reader-friendly, and linguistically appropriate health messages. Through this training, it is expected that Puskesmas can optimize the dissemination of accurate and easily understood health information, thereby raising public awareness of the importance of healthy living behavior. Keywords: training, health education content, Indonesian language, social media, Puskesmas